Policy of village fund in triangle analysis: literature review - Reginaldis, Maria Margareta; Andriastuti, Komang Tri Putri; Rumlus, Herman CMS (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
Implementation of policies regarding village fund allocation is expected to improve the welfare of village communities. However, the condition of rural communities in various developing countries is still far from prosperous. One of the factors is that village fund allocations are not implemented well. A new village fund policy implementation model is needed as well as an active role for the government and community to improve the policy implementation process. Limited involvement of the government, community and academics is also one of the determinants of improved implementation of village funds. This article will explain and complement research that has been carried out previously regarding the implementation of policies regarding village fund allocation using the triangle analysis model. This study was a review of relevant literature, and used Publish or Perish (PoP) software to find significant articles and conducted an article selection process to determine relevant articles. In this study, we examined 15 previous papers related to our topic. The results of this research show that there is still limited research on the implementation of policies regarding village fund allocation using the triangle analysis model in various countries. This article provides opportunities for further research using the triangle analysis model in the implementation of policies regarding village fund allocation.